Data quality in research data management: a bibliometric study - Piccolo, Daiane Marcela [UNESP]; Wolf Tadini, Antonio Victor [UNESP]; Teixeira, Heytor Diniz [UNESP]; Botega, Leonardo Castro [UNESP]; Goncalves Sant'Ana, Ricardo Cesar [UNESP]; Santarem Segundo, Jose Eduardo; Vesu Alves, Rachel Cristina [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2022)
Research data management is recognized by the scientific community as an important part of best practices in research, so that these data should be available for access and reuse. Within the context of research data management, data curation and data quality are understood as strategic elements. This work aims to characterize and specify the existing scientific production on the theme data quality in research data management through the measurement of bibliometric indicators. In methodological terms, this research has a quantitative and qualitative nature, is exploratory in its objectives and uses the Web of Science and Scopus databases to compose the corpus of the bibliometric study. As a result, it was identified from a corpus of 77 articles a period of relevant publications between the years 1984 and 2020, being 2019 the year with more published works. Additionally, 7 publication vehicles presented more than one publication for the researched topic, being the United States the country with more published papers, totaling 34 articles. The area of Computer Science was the one that produced the most on this topic and constitutes a trend in its interdisciplinarity with biological, applied social and health sciences. Finally, we conclude that, based on the awareness that data quality is a relative parameter, the implementation of research data management services must go through preparation, focusing on meeting requirements such as those concerning the domain and the intended uses.
Keywords: Research data management; Data quality; Research data; Scientific data; Digital curation